Conservative Management after Intraoperative Over-Release of the Medial Collateral Ligament from its Tibial Insertion Site in Patients Undergoing Total Knee Arthroplasty - Choi, Young Joon; Lee, Ki Won; Seo, Dong Kyo; Lee, Suk Kyu; Kim, Sang Bum; Lee, Hyun Il (The Journal of Knee Surgery, 2018)
During varus deformity correction in a patient undergoing total knee arthroplasty (TKA), the medial collateral ligament (MCL) could get completely detached from its distal insertion site. Our aim was to evaluate the (1) mid-term clinical outcome and implant survival after conservative treatment in patients with intraoperatively over-released MCL and (2) preoperative risk factors for MCL over-release. A retrospective study was conducted on patients who had undergone a primary TKA between 2001 and 2006. The number of knees with intraoperative MCL over-release (over-released group) was 47 (40 patients); we compared these with the knees that had intact MCL (intact group, 502 knees). Simple anchoring of MCL was performed with no additional protection. The postoperative clinical outcome and implant survival were compared. Risk factors for MCL over-release were identified using multivariate analysis. The average follow-up period was 7.5 years. The mean Knee Society score of the over-released group improved from 23.3 to 92.7 and it was not significantly different from the intact group. Three cases of aseptic loosening occurred in the over-released group and 19 in the intact group (p = 0.423). The survival rates of the implant were 94.4% and 96.1%, respectively, at 13 years postoperatively. Multivariate analysis showed preoperative femoral–tibial angle as the only risk factor for over-release. This study showed that even MCL was over-released inadvertently, but it did not affect the clinical outcome. Preoperative femoral–tibial angle was the only predictable risk factor for MCL over-release.
Keywords: knee; varus deformity; soft tissue balancing; medial collateral ligament